The Students’ Perceptions of Using Worksheet in English Online Learning at Ninth Grade Junior High School Number 2 Jambi City - Putriani Putriani; Suyadi Suyadi; Kartika Dewi (JELT: Journal of English Language Teaching, 2022)
This study aims to determine the students' perception of using worksheet in English Online Learning at the Ninth Grade Junior High School Number 2 Jambi City. This research methodology in this study is qualitative research design whose analysis setting of the research requires in-depth observation. The subjects of this study were students of class ninth grade junior high school number 2 Jambi city, was used Purposive sampling totaling six students as participants consisting of two students from low scores, two students from minimum scores, and two students from high scores and two students with high grades, and active students who get ranks from one to six. In collecting data this research gave interviews in class. The results showed that class IX students of SMPN 2 Jambi City this researchs found some difficulties in capturing meaning in the learning process using online worksheets but can help children's success in the process of learning English online. Worksheet can be    helps teachers and students in online learning so that students can use worksheet correctly and easily in implementing the application of worksheet in online learning.